2017
DOI: 10.1098/rspb.2016.2730
|View full text |Cite
|
Sign up to set email alerts
|

Excavation and aggregation as organizing factors in de novo construction by mound-building termites

Abstract: Termites construct complex mounds that are orders of magnitude larger than any individual and fulfil a variety of functional roles. Yet the processes through which these mounds are built, and by which the insects organize their efforts, remain poorly understood. The traditional understanding focuses on stigmergy, a form of indirect communication in which actions that change the environment provide cues that influence future work. Termite construction has long been thought to be organized via a putative 'cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…Density plots and averages of activity as a function of curvature for all orientations are shown in SI Figure A.6. While excavation and deposition cannot be separately quantified with our method, visual inspection showed that deposition occurred primarily in the immediate vicinity of excavation sites (SI Figures A.3-A.5), consistent with previous studies[10].Figure 2quantifies the correlation matrices between surface geometric factors (curvature, inclination and height) and both termite early locations and construction activity.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Density plots and averages of activity as a function of curvature for all orientations are shown in SI Figure A.6. While excavation and deposition cannot be separately quantified with our method, visual inspection showed that deposition occurred primarily in the immediate vicinity of excavation sites (SI Figures A.3-A.5), consistent with previous studies[10].Figure 2quantifies the correlation matrices between surface geometric factors (curvature, inclination and height) and both termite early locations and construction activity.…”
supporting
confidence: 87%
“…To investigate how these factors influence termite movement, we manually marked termite locations in each video at every 10 seconds for the first 5 minutes of each recording (for a total of 40 frames per replica). This time range was chosen in order to capture initial exploration activity, during a period before excavations began, since active excavation influences activity of other termites [10]. Since termites sometimes do not start moving for some time after being placed on the surface, we excluded termites that had not yet moved to a distance of at least 30 pixels from their positions in the first tracked frame.…”
Section: B Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There is another dimension of homeostasis at work here, engaging cognitive interactions of termites with soil. We have identified at least five such cognitive interactions, involving various aspects of mound maintenance, construction and repair [45,62,63]. One is the classic concept of stigmergy [57], which we prefer to call focal building, because it draws soil into foci of building.…”
Section: Extended Cognitionmentioning
confidence: 99%
“…Adapting such approaches to the case of construction by termites has likewise begun to provide new understanding [5], but faces distinct challenges that follow from the problem domain. In particular, tracking termite building activity involves tracking the movement of soil pellets created and manipulated by the termites.…”
Section: Introductionmentioning
confidence: 99%